How useful are crowdsourced air temperature observations? An assessment of Netatmo stations and quality control schemes over the United Kingdom - Jonathan Coney; Ben Pickering; David Dufton; Maryna Lukach; Barbara Brooks; Ryan R. Neely III (Meteorological Applications, 2022)
Abstract Observations of the real‐time state of the atmosphere are required in order to initialize numerical weather prediction (NWP) models. As NWP resolution improves, more observations are needed, to better capture regional variations in atmospheric conditions. In particular, surface observations are necessary to reflect conditions experienced on the surface. One proposed opportunity to increase the number of surface observations available for assimilation into NWP is to crowdsource the data from home weather stations. This study investigates the outdoor air temperature measurements made by Netatmo home weather stations, through validation against a calibrated laboratory chamber and by evaluating quality control schemes that are applied to a UK‐wide network of Netatmo stations. In a series of controlled lab experiments, it was found that the Netatmo temperature sensor was accurate to 0.3°C. The response to fluctuations in temperature is lagged, with τ (the time taken for 63% of the change to be measured) calculated as 12.7 min for a near‐instantaneous decrease in temperature. Netatmo temperature observations were compared with Met Office MIDAS hourly weather observations. A warm bias in excess of 1°C was present in the Netatmo temperature observations, which was lessened by the three quality control schemes tested, but still in excess of 0.5°C. Hence, Netatmo temperature measurements have potential to be assimilated in NWP in the United Kingdom, but work is required to find a suitable agreed quality control scheme to filter out anomalous observations in the United Kingdom.